Hulking out : Potentiating in vitro biocontrol activity against Fusarium oxysporum f. sp. cubense Tropical Race 4 (2025)
Fusarium oxysporum f. sp. cubense Tropical Race 4 is a plant pathogen of massive importance, as it can infect Cavendish banana and leave devastation behind in any plantation it reaches. As of today, the pathogen is managed via cultural practises and biocontrol strategies; and Colombia is a great example for both. Thanks to cultural practises and biosafety measures, the pathogen has been contained in a small number of farms in La Guajira and Magdalena departments, and Agrosavia (Corporación Colombiana de Investigación Agropecuaria) has been investing considerable effort into effective biocontrol strategies. One of these uses gamma-ray irradiation as a promising strategy for improvement of biocontrol activity, with direct in vitro antagonism tests against the pathogen, comparing direct antagonism capabilities between mutated microorganisms. Therefore, in this project, radiosensitivity assays were performed on biocontrol microorganisms, as well as antagonism tests to compare the antagonistic performance of irradiated microorganisms with their wild type counterparts. As a result, there were several irradiated colonies which outperformed their respective wild type colonies, and a library of primers for suggested molecular markers associated with antagonism processes was constructed. However, it was not possible to obtain lethal doses for any of the irradiated strains.